Analyzing Coherence and Cohesion in Sara Duterte's Vice Presidential Inaugural Speech - Sebalda, Resyl; Taray, Celeste Faye; Tulud, Donnie M. (International Journal of Language and Literary Studies, 2025)
This study examines the coherence and cohesion of Sara Duterte’s inaugural speech as the newly elected Vice President of the Philippines. It aims the grammatical and lexical cohesion devices used in the speech to understand their role in enhancing clarity and logical flow. Using a qualitative descriptive approach and content analysis, the study identifies linguistic features that contribute to coherence. Data were extracted from the official speech transcript and analyzed to assess the effectiveness of cohesive devices. The findings reveal that various cohesion methods such as references, repetition, and conjunctions were employed to maintain logical progression and emphasize key points. The study concludes that these linguistic strategies are essential for ensuring the speech's readability and persuasiveness. Furthermore, the findings unveil the significance of language and the role of coherence and cohesion in influencing public opinion, exercising power, and shaping identities in Philippine political discourse. By understanding these cohesion techniques, citizens can become more informed and critical consumers of political information, fostering greater awareness in public discourse.